Effect of dry salt versus brine injection plus dry salt on the physicochemical characteristics of smoked salmon after filleting - Astruc, Thierry; Vénien, Annie; Clerjon, Sylvie; Favier, Raphael; Loison, Olivier; Mirade, Pierre-Sylvain; Portanguen, Stéphane; Rouel, Jacques; Lethiec, Mailys; Germond, Arno (Heliyon, 2022)
International audience Smoked fish fillets are pre-salted as a food conservation and quality preservation measure. Here we investigated biochemical and sensory aspects of smoked salmon fillets. Left-side salmon fillets were dry-salted while the rightside fillets underwent a mixed salting method consisting of an injection of saturated brine followed by surface application of dry salt. After 6 h of salting, all the fillets were smoked. At each step of the process, quality was evaluated using instrumental measurements (pH, color, texture, water content, salt content, a w), and lipid distribution was visualized by MRI. Mixed-salted fillets had a higher salt content than dry-salted fillets and variability in salt distribution was dependent on the salting process. However, these variations had no effect on pH, color or texture, which showed similar values regardless of salting method. Fatty areas had a lower salt content due to slower diffusion of aqueous salt solutions through them. Mixed salting speeds up the salting of the muscle without significantly affecting the quality traits of the salmon fillet.